Knowledge and Practice of Nurses Regarding Infection Control Measures in Tertiary Care Hospital - kanwal, Ammara; Latif, Abida; bibi, Asima; Manzoor, Naheed; kousar, Farzana; Maqbool, Bushra (Biological and Clinical Sciences Research Journal, 2025)
Hospital-acquired infections (HAIs) pose a significant challenge to patient safety, particularly in low- and middle-income countries like Pakistan. Nurses play a critical role in preventing these infections through adherence to infection control measures. However, gaps in knowledge and compliance remain a significant concern in tertiary care settings. Objective: This study aimed to assess the knowledge and practices of nurses regarding infection control measures in a tertiary care hospital in Lahore, Pakistan. Methods: A cross-sectional observational study was conducted among 115 registered nurses working in various departments of a tertiary care hospital in Lahore. Participants were selected using a simple random sampling technique. Data were collected through a validated self-administered questionnaire assessing demographic characteristics, infection control knowledge, and compliance with standard precautions. Descriptive and inferential statistical analyses were conducted using SPSS version 23. The chi-square and independent t-tests evaluated associations between demographic factors and infection control knowledge and practice scores. Pearson’s correlation coefficient was applied to assess the relationship between knowledge and practice scores, with a significance level of p ≤ 0.05. Results: The majority of participants were female (84.7%), aged 22-30 years (56.7%), and had 1-5 years of clinical experience (55%). Regarding infection control knowledge, 28.1% had poor knowledge, 53.8% had fair knowledge, and 18.1% had high knowledge levels. Nurses with a BSN/MSN degree had significantly higher knowledge scores (p = 0.012) than those with a Post-RN diploma. Infection control practices were generally better, with 91.2% of nurses demonstrating high compliance, while only 2.2% exhibited poor adherence. Female nurses had significantly higher mean knowledge (p = 0.041) and practice scores (p = 0.004) than male nurses. A positive correlation was found between higher education levels and improved knowledge and practice scores, though experience did not significantly impact practice adherence. Conclusion: While most nurses adhered to infection control practices, gaps in knowledge were evident, particularly among those with lower educational backgrounds and male nurses. Targeted training programs and continuous education initiatives are necessary to enhance knowledge and compliance with infection control guidelines. Strengthening institutional policies and ensuring resource availability could improve adherence and reduce HAIs in Pakistan’s healthcare settings.